2022
DOI: 10.3390/jcm11092465
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Diagnostic Accuracy of the STANDARD M10 Assay for the Molecular Diagnosis of SARS-CoV-2 in the Point-of-Care and Critical Care Settings

Abstract: Accurate and rapid molecular diagnosis of COVID-19 is a crucial step to tackle the ongoing pandemic. The primary objective of this study was to estimate the real-world performance of the novel RT-PCR STANDARD M10 SARS-CoV-2 assay in a large number of nasopharyngeal (NP) specimens eluted in universal transport medium. The secondary objective was to evaluate the compatibility of this kit in testing NP samples eluted in an inactivated transport medium (essential for point-of-care testing) and lower respiratory tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Two other studies have also evaluated the STANDARD TM M10 SARS-CoV-2 assay for its use at POC sites. The first evaluation study estimated the sensitivity and specificity of the assay for the ORF1ab target at 95.5% (95% CI 91.7% to 97.6%) and 100% (95% CI 98.7% to 100%), respectively [20] . Furthermore, they also confirmed the lower LoD of the STANDARD TM M10 SARS-CoV-2 assay, compared to the reference methods they used.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies have also evaluated the STANDARD TM M10 SARS-CoV-2 assay for its use at POC sites. The first evaluation study estimated the sensitivity and specificity of the assay for the ORF1ab target at 95.5% (95% CI 91.7% to 97.6%) and 100% (95% CI 98.7% to 100%), respectively [20] . Furthermore, they also confirmed the lower LoD of the STANDARD TM M10 SARS-CoV-2 assay, compared to the reference methods they used.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a walk-away and random access all-in-one system processing the sample from extraction to results. Recent publications show that the performance of the STANDARD™ M10 SARS-CoV-2 with nasopharyngeal swabs is comparable to that of the main commercially available systems [ [20] , [21] , [22] ], but there isn’t yet no study about its use with stool samples. Given the on-demand nature of the test, its ease of set-up and its speed of execution (60 min), evaluating the performance of STANDARD™ M10 SARS-CoV-2 on fecal samples can greatly improve the detection of SARS-CoV-2 in donor material destined for FMT.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a comparative evaluation of 122 CE-marked Ag-RDTs by Scheiblauer et al [ 15 ] has demonstrated that the sensitivity of these assays may be as low as 0–30%. It is likely that this discrepancy is driven by the fact that the validation studies conceived by manufacturers for regulatory purposes may have low external validity as these evaluations are usually carried out on a limited number of well-characterized samples skewed towards high viral loads [ 17 ].…”
Section: Introductionmentioning
confidence: 99%